Analisis Penyelesaian Restitusi Pajak Pertambahan Nilai Sebagai Hak Wajib Pajak Di Kpp Pratama Jakarta Menteng Dua Tahun 2023 - Daeli, Nur Idaman; Singgih, Rahadi Pratomo (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Regulations containing the VAT refund policy are a right for every taxpayer. This research was conducted to analyze the settlement of value added tax refunds at KPP Pratama Jakarta Menteng Dua in 2023. The method used is a quantitative method with a descriptive approach. The results of the research show that the settlement of VAT refunds carried out at KPP Pratama Pratama Jakarta Menteng Dua is in accordance with procedures. Although existing regulations provide clear guidance for the tax authorities, technical and bureaucratic obstacles remain challenges. The collaborative work climate and facilities provided at KPP Pratama Jakarta Menteng Dua also support the completion of restitution. The main obstacles identified include taxpayers' lack of understanding of regulations, technical obstacles, and complicated bureaucracy. To overcome this obstacle, it is recommended to increase outreach and education, update information technology systems, and simplify procedures. This research emphasizes the importance of good understanding and effective coordination to improve the efficiency and quality of the VAT refund process.